MEASURING THE COLOR CHANGE OF POTATO STICKS AND PLANT OIL DURING FRYING PROCESSES - Tarek FOUDA; Nourhan KASSAB (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of this study is measuring the differences in color properties of potato sticks and oil by frying using Wock Skillet during three separate frying sessions. The measurements indicators were optical properties, RGB Bands: (Red, Green, Blue Bands), Intensity, and browning index of potato sticks and oil. The research was conducted in the laboratory of the Agricultural Engineering Department. The results showed a clear color change in the potato slices with the time of frying, and they also showed a clear color change in the number of times the oil was fried. The relationship between the oil browning index and the frying duration were happened. the oil browning index increased from 67.81 at the beginning of frying to 72.24 at the second minute, then to 75.18 in the fourth minute, then to 82.35 in the sixth minute, then to 84.49 in the eighth minute until it reached 87.75 at the tenth minute it end of the first frying process. The second frying time increased from 75.97 at the beginning of frying to 77.15 in the second minute, then to 78.92 in the fourth minute, then to 83.52 in the sixth minute, then to 86.93 in the eighth minute until it reached 88.18 in the tenth minute. In the third time also, the values increased from 76.44, 78.72, 82.54, 84.91, 88.53 and 90.15 in minutes 2, 4, 6, 8 and 10, respectively. While it was predicted that there would be a direct relationship between the potato browning index and the period of frying. And also, a direct relationship between the potato browning index and the number of frying times. as it increased from 48.11 in the fourth minute, then to 54.24 in the sixth minute, then to 61.83 in the eighth minute until it reached 69.50 in the tenth minute at the end of the first frying process.